Anterior cingulate cortex parvalbumin and somatostatin interneurons shape social behavior in male mice - Chuchu Qi; Wenqi Sima; Honghui Mao; Erling Hu; Junye Ge; Mao Deng; Andi Chen; Weiyi Ye; Qian Xue; Wenting Wang; Qian Chen; Shengxi Wu (Nature Communications)
Abstract The anterior cingulate cortex (ACC) is essential for social behavior, and its dysfunction is implicated in social interaction deficits in autism. Pyramidal neuron activity in the ACC is modulated by parvalbumin (PV) and somatostatin (SST) interneurons, though their specific roles in social interactions remain unclear. Here, we demonstrate that PV and SST interneurons differentially contribute to the regulation of social interactions. In a Shank3-deficient autistic model, the expression of Kcnh7, a risk gene for autism, is reduced in both PV and SST interneurons. Knocking out Kcnh7 in either interneuron subtype leads to social interaction deficits. Furthermore, projections from the lateral posterior thalamic nucleus (mediorostral part, LPMR) to PV interneurons and from the ventral hippocampus (vHPC) to SST interneurons differentially modulate social interactions. These findings provide new insights into the distinct roles of PV and SST interneurons in social processes and their contributions to autism-related pathophysiology.